Composition and Factorial Invariance for the Assessment of Body Image Dissatisfaction Questionnaire in Mexican Adolescents - Raúl Josué Nájera-Longoria; José René Blanco; Carolina Jiménez-Lira; Susana Ivonne Aguirre; Humberto Blanco; Miguel Conchas-Ramírez; Yunuen Socorro Rangel-Ledezma; Perla Jannet Jurado-García (MDPI AG, 2021)
Body image is a mental representation that a person has, which could become a body dissatisfaction due to the pressure exerted by the culture, affecting several life stages specially in adolescents. The aim of this study was to analyze the psychometric properties and factorial invariance of the questionnaire to assess body image dissatisfaction. The sample consisted of 552 Mexican teenagers, 259 female, and 293 male, with a mean age of 12.91 ± 0.96 years. Confirmatory Factor Analyses show that a five-factor structure is viable and adequate. The five-factor structure (perceptual, emotional distress, behavioral, proposal to change, and fear of gaining weight) show adequate fit indices and validity, even though the obtained model does not completely correspond to that proposed by the authors of the scale, it continues to endorse the multifactorial component of body dissatisfaction. On the other hand, the factorial structure, the factor loadings, and the intercepts are considered invariant in both populations; however, there are differences between the populations for the means of the perceptual, emotional distress, and fear of gaining weight factors. This study serves as a premise for future research on the study of instruments for measuring body image in populations with different personal and cultural factors.